Exploitation of heterosis, combining ability and gene action potential for improvement in okra (Abelmoschus esculentus) - PATHANIA, RAHUL; MEHTA, DEVINDER KUMAR; BHARDWAJ, RAMESH K; DOGRA, RAJESH K; SINGH, KHUSHWANT; KAPLEX, ABHISHEK; SHARMA, SHIFALI (The Indian Journal of Agricultural Sciences, 2024)
Exploitation of the heterosis, combining ability and gene action potential in okra [Abelmoschus esculentus (L.) Moench] serves to optimize breeding efficacy, enhance both yield and quality, and facilitate the development of disease resistant and adaptable varieties. The study was carried out during rainy (kharif) seasons of 2022 and 2023 at Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh to assess the combining ability and gene action potential for 14 fruit yield and related traits in 11 parental lines and their 24 crosses. The hybrid cross Neri-7×Punjab Suhawani was proven remarkably significant positive heterosis compared to both better parent (BP) and the standard check (SC) for yield and related characters. Among the parental lines, Neri-9 and Neri-11 revealed with superior general combining ability (GCA) for maximum traits. Crosses Neri-7×Punjab Suhawani followed by Neri-75×PB-5, Neri-M×Varsha Uphar, Neri-19×Punjab Suhawani, Neri-11×PB-5 and Neri-11×Varsha Uphar recorded with maximum significantly positive specific combining ability (SCA) for yield and related traits. The non-additive gene action was pronounced in governing all the traits as the ratio of general combining ability variance (σ2GCA) and specific combining ability variance (σ2SCA) was recorded less than one for all of the characters. Proportional contribution (in per cent) of the lines was recorded greater than the testers but it was recorded lower than line × tester for the maximum traits. The superior performing crosses Neri-7×Punjab Suhawani, Neri-75×PB-5, Neri-M×Varsha Uphar, Neri-19×Punjab Suhawani and Neri-11×PB-5 showed potential for producing F1 hybrids and releasing as superior recombinants after conducting several location trials.